Neonatal Septicemia: Isolation, Identification and Antibiotic Sensitivity Pattern of Bacteria in a Tertiary Hospital in Bangladesh - Afrin, Mahmuda; Siddique, Md Abdullah; Ahmed, Abdullah Akhtar; Islam, Md Nazrul; Sarker, Parimol Chandra; Showkath, Mohammad Sohel; Sharmin, Rezowana; Aktar, Arefa; Begum, Poly; Khanom, Tahera; et al. (Faridpur Medical College Journal, 2017)
A cross sectional descriptive study was done to find out the causative organisms and their antibiotic sensitivities in the Department of Microbiology in collaboration with the Department of Paediatrics, Rajshahi Medical College Hospital (RMCH), Rajshahi during the period of July 2014 to June 2015. A total of 116 blood samples were taken aseptically from patients who were suspected of neonatal septicemia. Blood was then inoculated in Brain heart infusion broth. Bacterial isolation, identification and antimicrobial susceptibility testing were done by standard microbiological methods. Among 116 cases, 33(28.4%) were found to be culture positive. The most commonly isolated causative agents of neonatal septicemia were Staphylococcus aureus 17(51.5%) followed by Escherichia coli 10(30.3%), Streptococcus pneumoniae 03(9.09%), Klebsiella pneumoniae 02(6.06%) and Pseudomonas aeruginosa 01(3.03%). In general, all the Gram positive and Gram negative isolates were highly sensitive to meropenem, amikacin, gentamicin and ciprofloxacin. Gram positive bacteria were found to be particularly sensitive to vancomycin. They were moderately sensitive to ceftazidime followed in amoxicillin but were totally resistant to ampicillin. This study revealed that Staphylococcus aureus and E.coli are predominant causative organisms in neonatal septicemia and these are highly sensitive to meropenem, amikacin, gentamicin and ciprofloxacin. Faridpur Med. Coll. J. Jul 2016;11(2): 58-61